(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Misings are an ethnic group of North –East India and is also a second largest group in Assam. The relation between the Ahom rulers and the Mising community of North East India can trace back to 17th century connection with trade, politico-economic etc. The earlier relations between the Mising and the Ahoms were decent. The Mising were appointed in various administrative services. Records have been found about the Mising accessions into the Ahom administration. Later, for the some reasons Mising raided the Ahom village